The Jewish Obligation to Stand Up against Islamophobia in the United States - Lisabeth Kaplan; Paul Roochnik (American Journal of Islam and Society, 2004)
First they came for the communists, and I did not speak out – because I was not a communist; Then they came for the socialists, and I did not speak out – because I was not a socialist; Then they came for the trade unionists, and I did not speak out – because I was not a trade unionist; Then they came for the Jews, and I did not speak out – because I was not a Jew; Then they came for me – and there was no one left to speak out for me. The German anti-Nazi Protestant minister, Martin Niemoeller, spoke these poignant words following the end of World War II. Pastor Niemoeller reminds us that whenever society singles out a specific minority for abuse, the rest of society must resist. What folly it is to believe that during a time of insecurity and suspicion, any minority – religious, ethnic, or political – can long enjoy immunity from oppression. The Jewish people, perhaps more than other minorities, has an intimate familiarity with the plight of the scapegoat, a 2,000 year history of diaspora and minority status, with all the cruelty and violence that has accompanied this experience. In this work, we will cite Biblical sources, cultural traditions, and rabbinic teachings to express the inescapable obligation of Jews to stand in solidarity with Muslims in their time of need. Make no mistake about it: Muslims now confront unprecedented discrimination and harassment in the United States. In a recent report, the American-Arab Anti-Discrimination Committee (ADC) reports a significant increase in the frequency of hate crimes and acts of discrimination perpetrated against Arabs (both Muslims and Christians) and non-Arab Muslims.1 The list includes hundreds of acts of physical violence, some 60 incidents of Arab or Muslim passengers being prevented from traveling on airlines simply because of their “profile,” several hundred employment discrimination cases, and serious concerns arising from the USA Patriot Act. Tabloid media and bigoted radio talk show hosts contribute to an atmosphere of Islamophobia, and some Americans associate the word “Muslim” or “Arab” with “terrorist.” Shortly after the 9/11 attacks, conservative pundit Ann Coulter, commenting on Arab and Muslim countries, suggested that “we should invade their countries, kill their leaders and convert them to Christianity.”2 An Islamophobic atmosphere has taken hold in the United States, targeting Muslims not for any crime, but merely for being Muslims ...